QUALITY OF LANDRACE PIG SEMEN DILUTED WITH COCONUT WATER, EGG YOLK AND PURPLE SWEET POTATO ETHANOL EXTRACT - Viana, Lindalva Maria Jerónimo; Bebas, Wayan; Trilaksana, I Gusti Ngurah Bagus; Pemayun, Tjok Gde Oka; Susari, Ni Nyoman Werdi; Laksmi, Desak Nyoman Dewi Indira (Buletin Veteriner Udayana, 2026)
The success of artificial insemination in livestock depends on the quality and quantity of semen used in order to maintain a quality of semen itself. Hence, an effort to minimize the declining of spermatozoa quality during preservation is made by diluting semen using a diluent that contains nutrients in the right proportion between the diluent and semen.This study aims to determine the effect of adding an ethanol extract obtained from purple sweet potato to a coconut water egg yolk-based diluent on the quality of Landrace pig semen. This research was carried out based on an experimental laboratory study with a Completely Randomized Design (CRD) using a selected Landrace pig semen, which was taken from a pig. The research was also conducted in order to observe variables which included motility, viability, abnormalities, intact plasma membranes, and intact acrosomal membranes. The research used four specific treatments such as: P0 (BTS® as control), P1 (coconut water), P2 (coconut water and egg yolk), and P3 (coconut water, egg yolk + purple sweet potato ethanol extract), with six replications for each treatment. The data were analyzed using analysis of variance (ANOVA). If significant differences were found (p<0.05), statistical testing was performed using Duncan's test. The results of analysis showed that the P3 treatment group had the highest values ​​(p<0.05) for motility and viability, at 47.16±0.40% and 58.83±0.40%, respectively, compared to the other treatment groups. The P3 treatment group showed the lowest value for abnormality at 6.00±0.00%, contributing to a decrease of abnormality in a sperm. Furthermore, observations of intact plasma membranes and intact acrosomal membranes also showed that the P3 treatment group had the highest percentages, at 59.33±0.51% and60.16±0.98%, compared to the other treatment groups. The results of this study indicate that the combination of three components in the P3 treatment provides optimal protection for sperm cell structure, particularly in terms of motility, viability, abnormalities, as well as integrity of intact plasma membranes and intact acrosomal membranes. The electrolyte content in coconut water, phospholipids in egg yolk, and anthocyanins from purple sweet potato extract are thought to work synergistically to stabilize cell membranes and reduce free radical damage. Therefore, the results of this study recommend the use of local natural materials as a functional alternative diluent in pig reproductive technology.